Multiomics identifies a cholesterol–TFEB–PLD3–TLR9 axis driving immunosuppressive tumor-associated macrophage polarization in esophageal squamous cell carcinoma - Licheng Tan; Hongyu Zhou; Baifeng Zhang; Dora Lai Wan Kwong; Yongxu Jia; Jiayi Huang; Kin To Hugo Siu; Shuang Zhang; Jiao Huang; Jie Luo; Yuma Yang; Qin Liu; et al. (Proceedings of the National Academy of Sciences, 2026)
Tumor-associated macrophages (TAMs) reshape the tumor immune microenvironment and promote tumor progression, yet the underlying mechanisms remain largely unclear. Through integration of single-cell RNA (scRNA) sequencing datasets from esophageal squamous cell carcinoma (ESCC), we identified a distinct protumoral macrophage population with elevated expression of phospholipase D3 (PLD3). Multiomics investigations revealed that high infiltration of these PLD3-high macrophages was associated with poor clinical outcomes in ESCC patients. Mechanistically, tumor cells secreted cholesterol to modulate the microenvironment. Upon the uptake by TAMs, cholesterol triggered the nuclear translocation of transcription factor EB (TFEB), which directly bound to the PLD3 promoter region and activated its transcription. The overexpressed PLD3 localized to lysosomes, enzymatically degrading single-stranded nucleic acids, thereby suppressing the activation of the toll-like receptor 9 (TLR9) pathway. This cascade ultimately impaired effector T cell function and sustained an immunosuppressive tumor microenvironment (TME). Notably, therapeutic intervention using ODN2216-siPLD3 in murine models enhanced CD8 T cell infiltration and significantly inhibited tumor growth. Our findings highlight PLD3-high macrophages as a promising diagnostic biomarker and a therapeutic target for ESCC, paving the way for potential clinical translation.